A Review of Thermal Fluid System and Thermal Transport - Vimal Sagar; Anita Sagar (AG Volumes, 2022)
A solar thermal system's efficiency, cost, and dependability are all significantly impacted by the heat transfer fluids used in the system. In this study, we use a novel figure of merit that takes into account the fluid's thermal storage capacity, its convective heat transfer properties, and its hydraulic performance to rank different types of heat transfer fluids including oils and molten salts. Safety, freezing point, and thermal stability considerations are also covered. Using a comparative study, we look at the advantages and disadvantages of several fluids for use in solar thermal heat transfer systems, such as water-steam combinations (direct steam), ionic liquids/melts, and suspensions of nanoparticles (nanofluids).